Keefektifan Penggunaan Desain dan Model Kerajinan Tangan untuk Pembelajaran Keterampilan Berkreasi Seni di SD - Sumanto Sumanto (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2002)
This classroom action research (CAR) was conducted to describe the effectiveness of the use of handicraft design and model in teaching arts. It implemented a cycle model involving planning, action, observation, and reflection. The subjects were fourth graders of the Laboratory Elementary School, Malang. Data were collected by using a participatory observation while the action was going on. The results indicated that handicraft design and model were always needed in teaching arts. The media helped improve the pupils' motivation in creating mosaics, sculptures, and reliefs.